2016
DOI: 10.4149/315_150930n510
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of chemotherapy and electrochemotherapy on ovarian cell lines in vitro

Abstract: The presented study aimed to evaluate in vitro the effectiveness of improvement standard chemotherapy with bleomycin by electroporation in two various ovarian cancer cell lines. Two human ovarian cell lines OvBH-1 and SKOV-3 were used. The lines were selected because of their resistance to several therapeutic methods. As anticancer drug we use range of concentrations of bleomycin. In EP and ECT experiments different voltage values: from 0 to 1200 V/cm, 8 pulses with duration of 100μs and intervals between puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before. 23,26 Furthermore, it was demonstrated that electrochemotherapy with cisplatin is a promising therapeutic approach for bladder cancer 20 and that it is more effective in HPV-positive than HPV-negative head and neck tumors.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before. 23,26 Furthermore, it was demonstrated that electrochemotherapy with cisplatin is a promising therapeutic approach for bladder cancer 20 and that it is more effective in HPV-positive than HPV-negative head and neck tumors.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…The available literature shows that physical methods, e.g., ultrasonic techniques (sonoporation) [13,14] or electroporation [15][16][17] in combination with chemotherapy, or electromagnetic treatment against antibiotic [18] or antimicrobial resistance [19], can be efficiently applied to overcome cell resistance in vivo and in vitro. Electrochemotherapy is based on the application of high-voltage electric pulses, causing permeabilization of membranes (electroporation) and increased drug uptake by cancer cells [20]. It is a pulse-dependent phenomenon, and usually, the microsecond range pulses are used [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most established applications of electroporation is the treatment of cancer [ 4 ]. This allows the minimization of the dosage of chemotherapeutic drugs [ 5 , 6 ] and/or adverse effects during the ablation of the tumor [ 7 ]. Consequently, the combination of chemotherapeutic drugs and electroporation was coined electrochemotherapy and is widely used in clinics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%